A study on Impact of Goods & service tax on the manufacturing sector in India - Sahoo, Bibhu Prasad; Dhanda, Upasana (International Journal of Psychosocial Rehabilitation, 2020)
India’s manufacturing sector has been growing gradually since the early 2000s, generating new employment opportunities and uplifting the economy. GST has the capability to amplify this growth with its streamlined tax structure and positive effect on interstate sales. The campaign “Make in India” by Narendra Modi gives further momentum to the manufacturing sector. Furthermore, Price Waterhouse Coopers estimates that India will become the fifth largest manufacturing country in the world by 2020. In such a scenario, it would be intriguing to understand the effect of GST on the manufacturing sector. The article discusses both pros and cons of this tax regime on the manufacturing sector and throws light on the potential reasons for its success and failure.